Measuring the Effectiveness and Innovative Capability: Case Lahti University Consortium - Sanna Pekkola; Juhani Ukko (European Financial and Accounting Journal, 2008)
The aim of this study is to create a measurement system for evaluating the effectiveness and innovative capability of the Lahti University Consortium. The Lahti University Consortium is a network university, which was established by four Finnish universities and offers services provided by departments of these universities. The empirical evidence of the study is based on interviews carried out in six organisations. The result of the study represents an evaluation matrix, which measures the effectiveness and innovative capability of the Lahti University Consortium. The evaluation matrix consists of four sectors and five dimensions. The study also reveals several challenges faced in designing and implementing a performance measurement system for the Lahti University Consortium.
Keywords: I23; 650; Effectiveness; Innovative capability; Public sector